Is Demonstrating against the Far Right Worth It? Evidence from French Presidential Elections - Nicolas Lagios; Pierre-Guillaume Méon; Ilan Tojerow (Institute of Labor Economics (IZA), 2022)
We study the electoral impact of protesting against the far right by investigating the demonstrations held during the 2002 French presidential elections against far-right candidate Jean-Marie Le Pen. Instrumenting rally attendance with rainfall while factoring in that some municipalities never host protests, we find that larger protests reduced both the number of votes for Le Pen and the number of abstentions, while increasing the number of votes for Chirac. Regarding the mechanisms behind these results, we show that protests reduced the social desirability of voting for Le Pen, the support for his policies, and generated spatial spillovers through local media.
Keywords: D72; 330; protest; election; demonstration; far right; populism